Defective Sn-Zn perovskites through bio-directed routes for modulating CO2RR. (October 2022) - Jiang, Junjie; Huang, Bosi; Daiyan, Rahman; Subhash, Bijil; Tsounis, Constantine; Ma, Zhipeng; Han, Chen; Zhao, Yufei; Effendi, Liyana Hasnan; Gallington, Leighanne C.; Hart, Judy N.; Scott, Jason A.; et al.
Abstract: Sn and Zn oxides can catalyze electrochemical CO2 reduction reactions (CO2 RR) to produce useful chemicals. Herein, we report on perovskite-type tin-zinc oxides (TZO) synthesized by a biomineralization approach under benign aqueous conditions. The resulting TZO catalysts are disordered and possess a high quantity of defects, which serve as highly reactive active sites in CO2 RR. Selectively toward formate or CO is tunable toward the relative amounts of Sn and Zn and their associated O defects. In-situ X-ray absorption spectroscopy measurements reveal electronic and structural transformations consistent with oxygen vacancy formation at Sn-O-Zn bridges as a function of cathodic potential that strongly correlates to CO2 RR selectivity. Density functional theory (DFT) calculations demonstrate that introducing an oxygen vacancy in TZO influences drastically influences formate/CO selectivity, consistent with our in-situ XAS findings and catalytic performance. Overall, these findings demonstrate the potential of biomineralization to fabricate perovskite-type metal oxides for energy conversion reactions. Graphical Abstract: Defective SnZn perovskites are generated by a biomineralization methodology for the electrochemical CO2 reduction reaction. Our graphical abstract showcases the affinity for formate or CO that is dependent on the ratio of Sn:Zn used in the synthesis, the materials were extensive characterized using synchrotron radiation methods and DFT calculations, as depicted within the graphical abstract. ga1 Highlights: Defective SnZn perovskites are synthesized by an aqueous biomineralization route. Selectively for CO2RR to CO or formate is established by tuning the Sn:Zn ratios. In-situ XAS measurements reveal the formation of O-vacancies during CO2RR. DFT calculations showcase improved reactivity at SnZn perovskites with O-vacancies.